Holistic Perspectives on Trauma 2015
DOI: 10.1201/b18313-9
|View full text |Cite
|
Sign up to set email alerts
|

Childhood Maltreatment and Coping in Bipolar Disorder

Abstract: Children who have experienced chronic parental rejection and exclusion during childhood, as is the case in childhood emotional maltreatment, may become especially sensitive to social exclusion. This study investigated the neural and emotional responses to social exclusion (with the Cyberball task) in young adults reporting childhood emotional maltreatment. Using functional magnetic resonance imaging, we investigated brain responses and self-reported distress to social exclusion in 46 young adult patients and h… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
10
0

Year Published

2015
2015
2019
2019

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 58 publications
1
10
0
Order By: Relevance
“…parental verbal abuse (Choi, Jeong, Rohan, Polcari, & Teicher, 2009;Tomoda et al, 2011), peer emotional abuse (Teicher, Samson, Sheu, Polcari, & McGreenery, 2010), harsh corporal punishment (Sheu, Polcari, Anderson, & Teicher, 2010;Tomoda, Suzuki, et al, 2009)]. Interestingly, some of the most recent studies have focused predominantly on subjects with emotional maltreatment (Hanson, Hariri, & Williamson, 2015;van der Werff et al, 2013b;van Harmelen, Hauber, et al, 2014;van Harmelen, van Tol, et al, 2014).…”
Section: Categories Of Maltreatmentmentioning
confidence: 99%
“…parental verbal abuse (Choi, Jeong, Rohan, Polcari, & Teicher, 2009;Tomoda et al, 2011), peer emotional abuse (Teicher, Samson, Sheu, Polcari, & McGreenery, 2010), harsh corporal punishment (Sheu, Polcari, Anderson, & Teicher, 2010;Tomoda, Suzuki, et al, 2009)]. Interestingly, some of the most recent studies have focused predominantly on subjects with emotional maltreatment (Hanson, Hariri, & Williamson, 2015;van der Werff et al, 2013b;van Harmelen, Hauber, et al, 2014;van Harmelen, van Tol, et al, 2014).…”
Section: Categories Of Maltreatmentmentioning
confidence: 99%
“…Future studies should also further investigate the more elusive subjective aspects of suicide risk, such as SI, as well as implicated psychological constructs such as hopelessness, rumination, and anhedonia [209][210][211], which may be relevant across diagnoses. Similarly, social experiences such as childhood maltreatment and peer bullying form a strong prelude to STB in later life [208,212,213], and impact on the neural structures implicated in STB (e.g., DMPFC structure and function [214,215]). Therefore, adverse experiences should be taken into account in future studies on the neurobiology of STB.…”
Section: Future Directionsmentioning
confidence: 99%
“…Several studies have demonstrated that maltreated children show an enhanced response to threatening facial expressions at the behavioural (Pollak et al., ) and neural levels, with altered functioning reported in the amygdala, anterior insula and prefrontal cortices (e.g. van Harmelen et al., ; McCrory et al., ). These structures have also been implicated in the psychopathology of affective disorders (Etkin & Wager, ) commonly elevated in individuals with maltreatment histories.…”
Section: Introductionmentioning
confidence: 99%
“…Two recent fMRI studies have aimed to assess the processing of more socially complex constructs in maltreated children. Using a Cyberball paradigm, which simulates the experience of social rejection, these studies have demonstrated that maltreatment experience is associated with heightened distress and altered neural activity to social rejection (van Harmelen et al., ; Puetz et al., ). The experience of social rejection is an established risk factor for psychopathology and poor academic performance in the population at large (Masten et al., ; Platt, Cohen Kadosh, & Lau, ; Sebastian, Viding, Williams, & Blakemore, ; Silk et al., ).…”
Section: Introductionmentioning
confidence: 99%